Janacek : - Wingfield, Paul (Cambridge University Press, 1992)
The Glagolitic Mass, written between 1926 and 1927, is not only one of Janá^D&cek's most important works: it is also a masterpiece of the twentieth-century choral repertoire. In this fascinating description of the Mass and its history, Paul Wingfield brings together information on all significant aspects of the work, including much that is new. In particular, he quotes important letters from and to the composer that have never previously been published.